Development of pedagogical content knowledge with regard to intersubjectivity and alterity - AKKOÇ, HATİCE (My University, 2009)
In this paper we focus development of pedagogical content knowledge (PCK) and examine this development in the light of the notions of intersubjectivity and alterity. We base our examination on data obtained from a teacher preparation program in which 20 teacher candidates take part. On the basis of the analysis of the data we argue that development of PCK is a dialogical process and such development could be described in terms of increasing intersubjectivity amongst the participants and that alterity, accounts for the different approaches adopted to leach a topic at hand in such a way that makes it comprehensible to the others.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Bilgisayar ve Öğretim Teknolojisi Eğitimi; Social Sciences and Humanities; Sociology; Education; Computer Education and Instructional Technology; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EĞİTİM, BİLİMSEL DİSİPLİNLER; Matematik; Temel Bilimler (SCI); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); EDUCATION, SCIENTIFIC DISCIPLINES; MATHEMATICS; Natural Sciences (SCI); Genel Sosyal Bilimler; Analiz; Cebir ve Sayı Teorisi; Matematik (çeşitli); Genel Matematik; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Analysis; Algebra and Number Theory; Mathematics (miscellaneous); General Mathematics; Physical Sciences; Social Sciences & Humanities